The Fourier transform and its applications - Bracewell, Ronald N. 1921-2007 (McGraw-Hill series in electrical and computer engineering : Circuits and systems, 2000)
"This electrical engineering text and professional reference explains transform methods and how to apply them to electrical subsystems: circuits, antennas, signal processors, and also to the interconnecting continuous-time signals, pulse sequences, and discrete time signals."--BOOK JACKET.